The lived experience of disadvantaged communities affected by the 2015 South Indian floods: Implications for disaster risk reduction dialogue. (15th February 2021) - Krishna, Revathi N.; Ronan, Kevin; Spencer, Caroline; Alisic, Eva
Abstract: Poverty and discrimination compound vulnerability to disasters. Yet, people who experience these are some of the least involved groups in Disaster Risk Reduction (DRR) dialogue and research. This study aims to fill that gap by narrating the lived experience of underprivileged flood-affected communities. We conducted in-depth interviews (N = 48) with community members (n = 36) and staff members of collaborating non-governmental organisations (n = 12). We also conducted focus group discussions with staff members of the same NGOs. The results describe how systemic issues entrenched with socio-economic and cultural factors impact a community's ability to prepare for floods. These communities received no warning or timely evacuation messages, and perceived the received support as inadequate and unfair. Communities recovered through their resourcefulness and thoughtfulness. They resented the government for its lack of action throughout the disaster cycle. Priorities for future efforts involve actively engaging these vulnerable groups and tailoring DRR activities for them.